2021
DOI: 10.31235/osf.io/be39q
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Populists Vote for Populists, Right? How Populist Attitude Scales Fail to Capture Support for Populists in Power

Abstract: Surveys of the attitudes of voters for populist parties generally measure three non-compensatory factors of populism: anti-elitism, people-centrism, and Manicheanism. Using Comparative Study of Electoral Systems Module 5 data for 23 countries, we evaluate whether this approach explains voting for populist parties across countries in Asia, Europe and the Americas. We show that the existing scale of populist attitudes effectively explains voting for populists in countries where populist leaders and parties are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…We run a confirmatory factor analysis (CFA) model and find only two factors with eigenvalues over one (2.56 and 1.18) and that, in line with our previous GRM analysis, pop2 displays the lowest unique variance (Table A2). Our analysis corroborates those by Castanho Silva et al (2020) and Jungkunz et al (2021) that also reveal important limitations regarding the choice of items by the CSES and other demand-side populism scales. The issues detected regarding goodness of fit, and unexpected loadings, indicate that at the failures predicting support for populist parties in some countries may be associated with the design of the scale.…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…We run a confirmatory factor analysis (CFA) model and find only two factors with eigenvalues over one (2.56 and 1.18) and that, in line with our previous GRM analysis, pop2 displays the lowest unique variance (Table A2). Our analysis corroborates those by Castanho Silva et al (2020) and Jungkunz et al (2021) that also reveal important limitations regarding the choice of items by the CSES and other demand-side populism scales. The issues detected regarding goodness of fit, and unexpected loadings, indicate that at the failures predicting support for populist parties in some countries may be associated with the design of the scale.…”
Section: Figuresupporting
confidence: 91%
“…Differences in the conceptualization-or emphasis on specific populist attributes-can also explain why some approaches work in some regional contexts but not so much in others (De la Torre and Mazzoleni, 2019, p. 81-85, 90-91). For instance, the emphasis on the anti-elite dimension can hinder the ability of some measurements to properly assess populism in countries where populist parties are in government (Jungkunz et al, 2021). Similarly, the conflation of populism with exclusionary right-wing nationalism in the literature (De Cleen and Stavrakakis, 2017) contributes to create some problems when it comes to measure attitudes and parties.…”
Section: Conceptualization Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous democracy research has indeed found that support for dimensions of democracy depends on the political context (Easton 1975;Spierings 2014). In a similar vein, Jungkunz, Fahey, and Hino (2021) find that the level of populist attitudes among voters for populist parties is lower when the populist party in question is in power. In contexts in which populist leaders are in power, the perceived importance of key institutions of liberal democracy, such as the separation of powers, is likely to be lower.…”
Section: Discussionmentioning
confidence: 70%
“…Estos análisis han tendido a ver las actitudes populistas como un constructo de orden superior de carácter no compensatorio, lo que implica que todos los componentes de las mismas deben estar mínimamente presentes para que podamos emplear este término (Wuttke et al, 2020). Estos desarrollos metodológicos han posibilitado la realización de análisis cuantitativos sobre la presencia (Akkerman, Mudde, and Zaslove, 2014), las causas (Spruyt et al, 2016;Akkerman, Zaslove y Spruyt, 2017;Rico et al, 2017;Marcos-Marne, 2021;Boscán et al, 2020;Stanojevic et al, 2020;Marcos-Marne et al, 2021) y los efectos de las actitudes populistas (Akkermann et al, 2014;Andreadis et al, 2013;Marcos-Marne et al, 2020;García Sanz et al, 2018;Jungkunz et al, 2021).…”
Section: El Populismo En La Ciencia Política Contemporánea: Marco Teó...unclassified